2022
DOI: 10.1177/00187208221113448
|View full text |Cite
|
Sign up to set email alerts
|

Drivers’ Evaluation of Different Automated Driving Styles: Is It Both Comfortable and Natural?

Abstract: Objective This study investigated users’ subjective evaluation of three highly automated driving styles, in terms of comfort and naturalness, when negotiating a UK road in a high-fidelity, motion-based, driving simulator. Background Comfort and naturalness play an important role in contributing to users’ acceptance and trust of automated vehicles (AVs), although not much is understood about the types of driving style which are considered comfortable or natural. Method A driving simulator study, simulating road… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(26 citation statements)
references
References 38 publications
(59 reference statements)
3
23
0
Order By: Relevance
“…Driving style is also about how the vehicle manoeuvre is influenced by road surface and geometry, such as how it negotiates different road curvatures, or whether the ride is smooth or jerky. A number of studies have investigated the link between changes in these aspects of a driving style, and user comfort in AVs (Dettmann et al, 2021;Elbanhawi et al, 2015;Hajiseyedjavadi et al, 2022;Hartwich et al, 2018;Peng et al, 2022;Summala, 2007). For example, Bellem et al (2018) propose a range of kinematics to assist with user comfort during different manoeuvres of highly automated vehicles, such as minimising acceleration and jerk -i.e.…”
Section: The Link Between Driving Styles and Comfortmentioning
confidence: 99%
See 4 more Smart Citations
“…Driving style is also about how the vehicle manoeuvre is influenced by road surface and geometry, such as how it negotiates different road curvatures, or whether the ride is smooth or jerky. A number of studies have investigated the link between changes in these aspects of a driving style, and user comfort in AVs (Dettmann et al, 2021;Elbanhawi et al, 2015;Hajiseyedjavadi et al, 2022;Hartwich et al, 2018;Peng et al, 2022;Summala, 2007). For example, Bellem et al (2018) propose a range of kinematics to assist with user comfort during different manoeuvres of highly automated vehicles, such as minimising acceleration and jerk -i.e.…”
Section: The Link Between Driving Styles and Comfortmentioning
confidence: 99%
“…the rate at which the acceleration changes with respect to time. Peng et al (2022) measured user comfort for two human-like and one machine-like driving style, and found that the replay of real human participants' driving (categorised as a "defensive" driving style -driving at lower speeds), was evaluated as more comfortable than the other two.…”
Section: The Link Between Driving Styles and Comfortmentioning
confidence: 99%
See 3 more Smart Citations